REAKSI SOSIAL MASYARAKAT TERHADAP FENOMENA ANAK SEBAGAI KORBAN SODOMI (Studi Kasus di Desa Rambah Kabupaten Rokan Hulu) - Nasri, Ahmad; Fakhri Usmita (Sisi Lain Realita, 2023)
The phenomenon of sexual violence against children is one of the social problems that requires serious treatment in order to be prevented. A sudden case of sodomy can be life-threatening and harmful both materially and mentally. The perpetrators who are still free to walk around always make children the target of the crime. The case of sodomy that occurred in the ruined village of Rokan Hulu district swallowed up the victims of children, which disturbed the community. Basically the world of children is just a play, but now their safety is threatened when there are still so many societies that are unconscious of this crime. This research aims to find out how society reacts to the phenomenon of children as victims of sodomy. The methodology used in this research is qualitative. The data collection techniques used are observations, interviews, and documentation. 11 research informants. The results of the research were: The reaction of the public to this case of sodomy, among other things, was to the people and the youth leader and followed up by the village chief. Then the village chief handed the perpetrators over to the Rambah Hilir police and the local police authority that handled the case has sentenced them in accordance with the Code of Human Rights and the Child Protection Article. The people of the village of Rambah collaborate with the village government and the youth chief take preventive measures to prevent the same crime from repeating again by limiting the activity of suspicious aliens and forming a village security team.